ARCHITECTURE AND MINERAL DEPOSIT SETTINGS OF THE ALTAID OROGENIC COLLAGE: A REVISED MODEL - Yakubchuk A. (My University, 2004)
The Altaids are an orogenic collage of Neoproterozoic–Paleozoic rocks located in the center of Eurasia. This collage consists of only three oroclinally bent Neoproterozoic–Early Paleozoic magmatic arcs (Kipchak, Tuva–Mongol, and Mugodzhar–Rudny Altai), separated by sutures of their former backarc basins, which were stitched by new generations of overlapping magmatic arcs. In addition, the Altaids host accreted fragments of the Neoproterozoic to Early Paleozoic oceanic island chains and Neoproterozoic to Cenozoic plume-related magmatic rocks superimposed on the accreted fragments. All these assemblages host important, many world-class, Late Proterozoic to Early Mesozoic gold, copper–molybdenum, lead–zinc, nickel and other deposits of various types.
Keywords: Altaid orogenic collage; Kipchak arc; Tuva–Mongol arc; Mugodzhar–Rudny Altai arc